Conventional and Islamic equity market reaction towards terrorism and disasters: an evidence based on type, location and Islamic calendar months - Irshad, Hira (2020)
Most prior researches have tested conventional equity market response towards terrorism and disasters. However, little attention has been paid to Islamic equity market. Besides, the equity market response towards terrorism and disasters based on the target/event type, event location and the Islamic calendar months has also remained underrepresented. The objective of this study is to investigate the conventional and Islamic equity market reactions towards terrorism and disasters in Pakistan based on the target/event type, event location and Islamic calendar months. In this regard, data from the year 2009 to 2016 was analyzed using Ordinary Least Square (OLS) regression and Generalized Autoregressive Conditional Heteroskedasticity (GARCH) (1,1) models. The key findings of the study indicate that the conventional and Islamic equity market reactions towards terrorism and disaster events are very short lived. The equity markets in Pakistan respond negatively to attacks on educational institutes and businesses whereas reacts positively to attacks on armed forces’ facilities. The equity markets respond negatively to the earthquakes and positively to the storm and extreme temperature. The conventional equity market responds negatively to the terrorist attacks in Karachi and positively to the attacks in financial cities and Federally Administered Tribal Areas (FATA). Islamic equity market responds positively towards attacks in financial cities and FATA. However, coefficient values are small which indicate very minor reaction magnitude. Likewise, the equity markets are insensitive towards disaster locations with exception of Gilgit. Overall, this study finds little evidence that conventional and Islamic equity markets react towards terrorism and disasters, whereas, the markets reactions vary based on event/target type, event location and different Islamic calendar months. The positive equity market response towards attacks on armed forces indicates the investor perception that armed forces are confronted with terrorist groups. The government may restore the investor confidence by initiating counterterrorism policies.